Implementation of New Student Registration Information System and Web-Based Tuition Fee Administration Management - Anas Al Marzaq; Dien Novita (Komunitas Dosen Indonesia, 2026)
The advancement of information technology has encouraged educational institutions to adopt digital transformation in various administrative processes, including the New Student Admission (PPDB) system. Manual PPDB procedures often lead to issues such as data entry errors, delays in document verification, and limited transparency for parents and school administrators. These challenges highlight the need for an automated system that streamlines the entire registration workflow. Therefore, this study aims to develop a web-based PPDB system that can address administrative problems encountered at SDIT Kamiliyah Palembang. The objective of this research is to design and implement an integrated information system that effectively supports online registration, document verification, and payment management. The Rational Unified Process (RUP) was applied, comprising the Inception, Elaboration, Construction, and Transition phases, to ensure systematic development aligned with user requirements. The results indicate that the system successfully facilitates online registration, document uploading, administrative verification, payment processing, and real-time information presentation through a dashboard. Black-Box Testing confirms that all functionalities operate as defined. Furthermore, the simplified user interface enhances usability and makes it easier for users to understand the registration flow. In conclusion, the web-based PPDB system effectively improves administrative efficiency and enhances transparency in the school's admissions process. This implementation contributes to the digitalization of educational services and may serve as a practical model for other schools with similar needs.